Application of Color Code Music Notation in Learning Piano for Early Childhood - Putra, Zakarias Aria Widyatama (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Introducing piano instruments to young children can significantly enhance their cognitive and academic development. This study delves into the effectiveness of using